Analisis Kelayakan Usahatani Padi Sebelum dan Setelah Mengikuti Program Makmur di Kecamatan Tempuran dan Kecamatan Pedes Kabupaten Karawang - Khairunnisa, Khairunnisa; Bakar, Abu; Wijaya, I Putu Eka (Jurnal Ilmiah Wahana Pendidikan, 2024)
The increase in agroinput prices caused a decrease in farmers' income, which prompted PT Pupuk Kujang to implement the Makmur Program to support farmers' capital supply. This research aims to analyze the comparison of production costs, revenues, income and feasibility of rice farming before and after the Makmur Program. This research was carried out in Tempuran District and Pedes District, Karawang Regency, taking the entire population of 30 people. Researchers carried out observations, interviews and documentation in this research. Data analysis using cost, revenue, income analysis, and feasibility analysis using R/C ratio and BEP analysis. The average production cost before the Makmur Program was Rp14,507,334.00/ha/MT, while after the Makmur Program it was Rp14,690,611.00/ha/MT. The average revenue before the Makmur Program was Rp24,572,116.00/ha/MT, while after the Makmur Program it was Rp23,307,667.00/ha/MT. The average income before the Makmur Program was Rp10,064,782.00/ha/MT, while after the Makmur Program it was Rp8,617,056.00/ha/MT. The average value of the R/C ratio before the Makmur Program was 1.75, while after the Makmur Program it was 1.63. The revenue BEP before the Makmur Program was Rp4,372,247.00/ha/MT, the price BEP was Rp2,576.00/kg, and the production BEP was 1,016.80 kg, while the BEP revenue after the Makmur Program was Rp4,886,722.00/ha/MT, BEP price Rp3,106.00/kg, and BEP production 1,018.07 kg. This research concludes that rice farming before and after the Makmur Program is feasible even though there is a decrease in income and feasibility after the Makmur Program.